MEDIA AUDIOVISUAL SEBAGAI SARANA MENINGKATKAN KEMAMPUAN MEMBACA PUISI SISWA KELAS VII SMP (AUDIOVISUAL MEDIA FOR IMPROVING SEVENTH-GRADE JUNIOR HIGH SCHOOL STUDENTS' POETRY READING SKILLS) - Nilawati, Nilawati; Rokhmansyah, Alfian; Prakoso, Teguh (Universitas Lambung Mangkurat, 2025)
AbstractAudiovisual Media for Improving Seventh-Grade Junior High School Students' Poetry Reading Skills. This study aims to improve the poetry reading skills of seventh-grade students at SMP Al-Faqih through the implementation of audiovisual media in Indonesian language classes. The research employed a Classroom Action Research (CAR) method with a descriptive qualitative approach, carried out in two cycles, each comprising the stages of planning, action, observation, and reflection. Data were collected through participatory observation and poetry reading tests. The results show a significant and progressive improvement in students' poetry reading skills. In the initial data, the classical completeness percentage was only 44.3%. After the audiovisual media was implemented in Cycle I, the completeness percentage increased to 60%. Despite this improvement, some students still showed a lack of confidence when reading poetry aloud, and the completeness target was not fully met. To address these challenges, the learning strategy was improved in Cycle II, focusing on more intensive teacher support and encouragement. As a result, the classical completeness percentage increased sharply, reaching 80% with an average class score of 80%. This improvement was also supported by a much higher student enthusiasm and active participation during the learning process, demonstrating the effectiveness of audiovisual media in creating an interactive and enjoyable learning environment. Thus, audiovisual media proved to be an effective choice for enhancing students' learning outcomes and appreciation for poetry.Keywords: Poetry reading skills, Audiovisual media, Classroom action researchAbstrakMedia Audiovisual sebagai Sarana Meningkatkan Kemampuan Membaca Puisi Siswa Kelas VII SMP. Penelitian ini bertujuan untuk meningkatkan kemampuan membaca puisi siswa kelas VII SMP Al-Faqih melalui penerapan media audiovisual pada materi puisi mata pelajaran Bahasa Indonesia. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan pendekatan deskriptif kualitatif, dilaksanakan dalam dua siklus yang masing-masing meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Data dikumpulkan melalui observasi partisipatif dan tes membaca puisi. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemampuan membaca puisi siswa secara progresif. Pada data awal, persentase ketuntasan klasikal hanya mencapai 44,3%. Setelah diterapkan media audiovisual pada siklus I, persentase ketuntasan meningkat menjadi 60%. Meskipun terjadi peningkatan, sebagian siswa masih menunjukkan ketidakpercayaan diri saat membacakan puisi, dan target ketuntasan belum sepenuhnya tercapai. Untuk mengatasi tantangan tersebut, perbaikan strategi pembelajaran dilakukan pada siklus II dengan fokus pada dukungan dan dorongan guru yang lebih intensif. Hasilnya, persentase ketuntasan klasikal meningkat tajam dan mencapai 80%, dengan rata-rata nilai kelas 80%. Peningkatan ini juga didukung oleh antusiasme dan partisipasi aktif siswa yang jauh lebih tinggi selama pembelajaran, menunjukkan efektivitas media audiovisual dalam menciptakan lingkungan belajar yang interaktif dan menyenangkan. Dengan demikian, media audiovisual terbukti menjadi pilihan yang efektif untuk meningkatkan hasil belajar dan apresiasi siswa terhadap puisi.Kata-kata kunci: Kemampuan membaca puisi, Media audiovisual, Penelitian tindakan kelas